Order and securityin Southeast Asia essays in memory of Michael Leifer - Liow, Joseph Chinyon, 1972-; Emmers, Ralf, a974- (Routledge politics in Asia series.)
Michael Leifer, who died in 2001, was one of the leading scholars of Southeast Asian international relations. He was hugely influential through his extensive writings and his contacts with people in government and business in the region. In this book, many of Leifer's students, colleagues and friends come together to explore the key themes of his work on Southeast Asia, including the notion of 'order', security, maritime law and foreign policy. The book concludes with an overall assessment of Leifer's background, worldview and impact on his field. A scholarly and personal volume devoted to Leifer's vast contributions to the discipline of international relations, this text is a must-read for students and scholars specializing in the region.